2006
DOI: 10.1128/jcm.01447-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Gen-Probe Transcription-Mediated Amplification Trichomonas vaginalis Research Assay and Real-Time PCR for Trichomonas vaginalis Detection Using a Roche LightCycler Instrument with Female Self-Obtained Vaginal Swab Samples and Male Urine Samples

Abstract: This study compared two assays for Trichomonas vaginalis detection, Gen-Probe's transcription-mediated amplification (TMA) assay for Trichomonas vaginalis and BTUB FRET PCR, using self-obtained clinical samples from 611 patients. Infection status was defined as two positive results by two different tests. The initial TMA assay sensitivity was 96.7%; specificity was 97.5%. The TMA assay was comparable to BTUB FRET PCR.Trichomonas vaginalis is the cause of the most common parasitic sexually transmitted infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 32 publications
(22 reference statements)
3
53
0
2
Order By: Relevance
“…Previous studies compared the ATV assay with nonmolecular assays for T. vaginalis detection, such as wet mount microscopy and culture, and showed that the ATV assay exhibited superior performance (15,17,(22)(23)(24). Other studies have shown that ATV performance is comparable to that of noncommercial PCR assays (12,24). This study is the first comparing the ATV assay side by side with another commercially available molecular assay (BD Affirm VPIII assay) for T. vaginalis detection.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies compared the ATV assay with nonmolecular assays for T. vaginalis detection, such as wet mount microscopy and culture, and showed that the ATV assay exhibited superior performance (15,17,(22)(23)(24). Other studies have shown that ATV performance is comparable to that of noncommercial PCR assays (12,24). This study is the first comparing the ATV assay side by side with another commercially available molecular assay (BD Affirm VPIII assay) for T. vaginalis detection.…”
Section: Discussionmentioning
confidence: 86%
“…A paucity of studies has examined the role of laboratory diagnosis for management of trichomoniasis in men (2,12,25,28). One of these studies (28) utilized DNA amplification technology to demonstrate detection of T. vaginalis in a greater proportion of asymptomatic males (51.4%) than in those with symptoms (23%; P ϭ 0.009).…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of clinical T. vaginalis ASR screening, subsequent validation of female urine specimens, along with male urethral and urine specimens (12), was completed. The present report describes findings from a 3-year audit of clinical T. vaginalis ASR (subsequently marketed as the APTIMA Trichomonas vaginalis assay with U.S. Food and Drug Administration indications for female urine and genital swab testing) screening of a largely subacute care demographic.…”
mentioning
confidence: 99%
“…ATV was highly specific for T. vaginalis (Ն98.9%) (28). Additional U.S. studies demonstrated that ATV has the highest sensitivity (Ͼ95%) in vaginal fluid of the available assays, including PCR, and has similarly high sensitivity in other sample types (urine, ES, and PCyt) (3,13,16,18,25). Andrea and Chapin demonstrated that the sensitivity of Affirm was only 64% in a comparison with ATV (3).…”
mentioning
confidence: 99%